Weight loss methods of high school wrestlers - Kiningham, R. B.; Gorenflo, D. W. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purpose of this investigation was to assess the weight loss practices of Michigan high school wrestlers at all levels of competition. Methods: A two-page survey was designed to assess weight loss behaviors of high school wrestlers. It was mailed by the Michigan High School Athletic Association (MHSAA) midway through the wrestling season to all Michigan high schools participating in interscholastic wrestling. Results: Completed surveys were received from 2532 wrestlers. Wrestlers lost an average of 6 pounds during the season. Over 50% of wrestlers lost more than 5 pounds; 27% of wrestlers lost at least 10 pounds; 72% of wrestlers engaged in at least one potentially harmful weight loss method each week of the wrestling season; 52% used at least two methods each week; 12% used at least five methods each week. Weekly use of laxatives, diet pill, or diuretics was reported by 2% of wrestlers. Vomiting to lose weight was done at least weekly by 2% of wrestlers. Wrestlers who engaged in at least one rapid weight loss method per week lost more weight, began wrestling at an earlier age, and reported more binge eating compared with wrestlers who did not report weekly rapid weight loss. Conclusion: The majority of Michigan high school wrestlers engaged in at least one potentially harmful weight loss method each week of the wrestling season. Fasting and various methods of dehydration were the primary methods of rapid weight loss. Wrestlers who lost weight each week were more likely to binge eat. Potentially harmful weight loss practices were found to be common at all grades and success levels.